Mood profiles and overtraining syndrome: a systematic review - Bonin, G. T.; Serafim, T. T.; Andrade, A. (Sport Sciences for Health, 2025)
Introduction Overtraining syndrome (OS) is characterized by imbalances between training load and recovery, resulting in fatigue, decline in performance, and emotional changes. These changes can negatively impact the mental health and sports career of athletes. The aim of this review is to investigate the association between mood profiles and OS, as well as to identify psychological markers relevant to diagnosis and prevention.